1D Simulation Modeling for an Exhaust Aftertreatment System SCR Calibration Modeling in GT-SUITE - Ramanjaneyalu, Puneeth (My University, 2021)
The Euro legislative regulations are imposed successively to hold back toxic elements that are harmful to the environment. Carbon monoxide (CO), hydrocarbons (HC) and nitric oxide (NOx) are the major toxic elements that cause serious health hazards for the living species. From many research works, selective catalytic reduction (SCR) is the most promising technology to address NOx. The objective of this project is to develop a surface reaction mechanism model, reaction rate calibration for SCR catalyst and validation. Firstly, building the SCR catalyst and surface reaction mechanism model in GTSUITE. The reaction rate calibration or characterization is performed for six reaction rate expressions with 18 unknown parameters by applying physical properties of the catalyst for example diameter and area of the catalyst. Furthermore, the digital laboratory Simulink black-box is utilized to produce the target reaction rate curves for all chemical reactions to calibrate the parameters then to compare with simulated GT-model results. Finally, validation for steady state or urea stairs, US, conditions and transient driving cycle conditions against WHTC (world harmonized transient driving cycles) for the Euro V regulations using tail pipe, engine-out emissions, mass flow rate and temperature traces experiments data. Overall, chemical kinetics modeling for SCR catalyst in GT-SUITE was successfully implemented and have reasonable results for urea stair cases, but the outcome can be further improved for transient cycles by extract information from 3D CFD to 1D in the future. Inevitably, simulations analysis is the best possible way to validate the results in quick time with low cost and it is a key factor during the development process.
Keywords: SCR, catalyst, chemical kinetics, validation, modeling, simulations, calibration and experiment data